T13. THE ASSOCIATION BETWEEN CHILDHOOD TRAUMA AND INFLAMMATION IN YOUTH AT CLINICAL HIGH RISK FOR PSYCHOSIS - Kelsven, Skylar (Schizophr Bull, 2019)
BACKGROUND: Childhood adversity is strongly associated with increased risk for psychosis. Research on the relationship between childhood adversity and psychosis not only links childhood abuse and neglect to psychotic symptoms, specifically hallucinations, but also indicates that the relationship is causal, with a dose-effect. Preliminary evidence of this relationship has been replicated within the clinical high risk (CHR) population through the North American Prodrome Longitudinal Study (NAPLS) where, relative to controls, individuals at CHR reported having experienced significantly more trauma and bullying, resulting in higher levels of anxiety and depression, as well as poorer functioning. Indices of stressful life events, family history of psychotic illness, and trauma represent robust predictors for presence of CHR syndrome and are included as part of the NAPLS Individualized Risk Calculator for Psychosis. Despite clear evidence for an association between childhood trauma and psychosis, the biological mechanisms that mediate this relationship remain largely unknown. Previous research has implicated the role of hypothalamic-pituitary-adrenal (HPA) axis dysregulation in development of both physical and mental illness. The HPA axis is highly responsive to environmental adversities both in childhood and in adulthood. Further, the HPA-axis is known to be a powerful modulator of inflammatory activity, as measured by peripheral markers of inflammation, and is in turn modulated by inflammatory processes. Immune system activation and dysregulation may serve as a biological mediator between childhood trauma and vulnerability for developing psychosis. The aim of this paper is to establish whether early-life adversity is associated with a pro-inflammatory phenotype in individuals at CHR for psychosis using a validated multiplex blood assay index previously established by Perkins et al. (2014). METHODS: 35 healthy controls and 62 CHR subjects (N=117) that participated in the NAPLS2 study, ages 12–35, were included. 32 of the CHR subjects later converted to psychosis. Experience of trauma was assessed using the Childhood Trauma and Abuse Scale, a semi‐structured interview used to detect the occurrence of psychological bullying, physical bullying, emotional neglect, physical abuse, psychological abuse, or sexual abuse, before the age of 16. Experience and sensitivity to stressful life events was assessed using a modified version of the Life Events Scale (LES). Subjective stress for endorsed items is coded on a 7-point Likert scale. Inflammation and oxidative stress were measured using a 15-analyte blood biomarker index previously established to reliably distinguish between healthy control subjects, CHR subjects who developed psychosis, and CHR subjects who did not develop psychosis. RESULTS: Across subjects, the 15-analyte index was significantly correlated with total number of unique traumas endorsed. Increased trauma exposure was associated with a higher analyte index value (r= .26, p< 0.01). Additionally, the 15-analyte index was significantly correlated with total number of reported undesirable life events (r=.20, p<0.05), as well as subjective level of stress to events (r=.26, p=0.01). Higher incidence of stressful life events, and increased level of subjective stress were associated with a higher analyte index value. DISCUSSION: These results provide preliminary evidence for an association between blood-based markers of inflammation, oxidative stress, and early-life adversity. Greater exposure to trauma, higher incidence of stressful life events, and increased levels of subjective stress to life events may be predictive of later life immune system activation.